Synthesis and SAR of novel isoxazoles as potent c-jun N-terminal kinase (JNK) Inhibitors - He, Yuanjun (Bioorg Med Chem Lett, 2013)
The design and synthesis of isoxazole 3 is described, a potent JNK inhibitor with two fold selectivity over p38. Optimization of this scaffold led to compounds 27 and 28 which showed greatly improved selectivity over p38 by maintaining the JNK3 potency of compound 3. Extensive SAR studies will be described as well as preliminary in vivo data of the two lead compounds.